CHARACTERIZATION OF LIPASE IMMOBILIZED ONTO CARRIER CHITOSAN-Fe3O4 BY THE COVALENT COUPLING METHOD - Dong, Bui Xuan; My, Pham Thi; Anh Thi, Huynh Van (Vietnam Journal of Biotechnology, 2018)
Enzymes are catalysts for biochemical reactions in the cell's metabolism. Enzymes are highly specific in their action on substrates. Lipase (triacylglycerol acylhydrolase) is an unique enzyme which can catalyze various types of reactions such as hydrolysis, esterification, alcoholysis… In recent days, studying and applying immobilized lipase in catalyzing transesterification of biodiesel production has been receiving much attention. The increased demand for biodiesel and the difficulties in obtaining enough quantities of raw materials for its production are stimulating the search for alternative feedstocks. Among the various possibilities, the utilization of residual fatty materials, in particular oils and animal fat residues from the meat and fish processing industries, are increasingly seen as viable options for biodiesel production. This paper presents the results of producing fixed lipase enzyme on microparticle chitosan-Fe3O4. Microparticle is a complex of nano particles Fe3O4 being absorbed on chitosan so it has magnetic property. Enzyme links to microparticle through an intermediate bridge – glutaraldehyde. Free enzyme which is used to fix is commercical lipase enzyme of Sigma (Germany) being extracted from pancreas of pig. Under the optimum conditions (pH 6, 40oC), after 3 hours reaction, immoblized enzyme activity measured 185 IU/mg and the productivity of attaching lipase to the carrier ratio was 75.1%. With immobilized lipase, the result of testing the biodiesel synthesized by lipid from wastewater of the surimi fish fillets manufacturing. The fuel properties of the biodiesel were further analyzed. The characterizations of the produced biodiesel showed that it met Vietnam standart (TCVN 7717:2007). Also discussed are the questions related to the viability of using this type of feedstocks in biodiesel production.